The effect of home care on readmission and mortality rate in patients with diabetes who underwent general surgeries - Lila Faridani; Parvaneh Abazari; Maryam Heidarpour; Hamid Melali; Mojtaba Akbari (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: More than one-half of people with diabetes need at least one surgery in their lifespan. Few studies have addressed how to manage the needs of these patients after discharge from the hospital. The present study is designed to determine the effect of home care on readmission of Type 2 diabetic patients who underwent surgical procedures. MATERIALS AND METHODS: The present study was a randomized clinical trial. Sixty-nine patients with Type 2 diabetes undergoing surgery were assigned to the intervention and control groups via blocking order in the selected educational hospitals of Isfahan 2019. Home care was performed for 3 months with interprofessional team approach. Data collection tools were re-admission checklist. Data were entered in SPSS software version 23 and were analyzed by nonparametric tests. RESULTS: The background characteristics in the intervention and control groups were not different. The frequency of readmission in the control and intervention groups from the time of discharge until 3 months later was 25.7% and 18.9%, respectively. Frequency of readmission in the intervention and control groups was not significant in 3 months from discharge, P > 0.05. The mortality rate was 11.4% and 0% in control and intervention groups, respectively, P < 0.05. CONCLUSION: It can be argued that continued home care can decrease the rate of readmission and mortality rate in patients with Type 2 diabetes who will discharge from surgical wards.